A Novel High‐Energy Hybrid Supercapacitor with an Anatase TiO2–Reduced Graphene Oxide Anode and an Activated Carbon Cathode. Issue 11 (9th July 2013) - Kim, Haegyeom; Cho, Min‐Young; Kim, Mok‐Hwa; Park, Kyu‐Young; Gwon, Hyeokjo; Lee, Yunsung; Roh, Kwang Chul; Kang, Kisuk
Abstract A hybrid supercapacitor with high energy and power densities is reported. It comprises a composite anode of anatase TiO2 and reduced graphene oxide and an activated carbon cathode in a non‐aqueous electrolyte. While intercalation compounds can provide high energy typically at the expense of power, the anatase TiO2 nanoparticles are able to sustain both high energy and power in the hybrid supercapacitor. At a voltage range from 1.0 to 3.0 V, 42 W h kg−1 of energy is achieved at 800 W kg−1. Even at a 4‐s charge/discharge rate, an energy density as high as 8.9 W h kg−1 can be retained. The high energy and power of this hybrid supercapacitor bridges the gap between conventional batteries with high energy and low power and supercapacitors with high power and low energy.